Theatrical and art activities in the internment camp of the Ukrainian Galician army in Josefov, Czechoslovakia (1922-1924) - Срібняк, Ігор; Срібняк, Мілана (Київський національний університет імені Тараса Шевченка, 2017)
Performances of cultural and art ensembles in Josefov played an important role in raising the morale of the internees, satisfying their nostalgic feelings towards their home and native land.  Actors and singers of the camp were given the opportunity for self-realization and development of their artistic abilities. Important was also that all without exception amateur activities related to the theater and performances were national in content and spirit and contributed to the spiritual consolidation of Ukrainian soldiers. In the repertoire of the camp theater Ukrainian household and historical plays dominated, because they corresponded the interest of the interned. One could name here, in particular, «Zaporozhets za Dunayem» [Cossack Beyond the Danube] by Semen Hulak-Artemovsky and «Marusya Bohuslavka» by Mykhailo Starytsky, for the production of which the theater section of the Cultural and Educational Club prepared a rich stage requisite and various scenery (for several acts). Women (wives of some interned) and their children had actively participated in the performances, which allowed to show events in the plays naturally. It should also be noted that during several years spent in the camp, artists have reached a fairly high level of skill. The artistic component of the camp life was duly represented at the exhibition which was installed in the camp. Due to this exhibition, creative achievements of amateur theatre clubs became known among the general public of the town of Josefov and the district. The significance of the camp theatres also consisted in the fact that Ukrainian song, music, dramatic art disseminated among Czech society a positive vision of Ukraine as a part of the European political and national-cultural space. The most important was that the interned searched and found their own original expression for their artistic quest, thus making its own contribution to the treasury of Ukrainian and European culture.

У статті проаналізовано окремі прояви театрально-мистецького життя інтернованих вояків-українців Української Галицької Армії у таборі Йозефов, Чехословаччина у 1922-1924 рр. Встановлено, що виступи таборових культурно-мистецьких гуртків у Йозефові мали важливе значення для піднесення морального духу та духовної консолідації українського вояцтва. Цій же меті слугувало проведення виставки досягнень інтернованих, яка була розгорнута у таборі для широкого загалу мешканців міста Йозефов та його округи.
Діяльність театрально-мистецьких осередків у таборі інтернованих вояків УГА Йозефов, ЧСР (1922-1924 рр.)
Keywords: theater; concert; exhibition; performance; repertoire; interned; Ukrainian Galician Army; театр; концерт; виставка; вистава; репертуар; інтерновані; Українська Галицька Армія